High dose-rate endoluminal brachytherapy for primary and recurrent esophageal cancer - Nicolay, Nils; Rademacher, Johanna; Oelmann-Avendano, Jan Tobias; Debus, Jürgen; Huber, Peter E.; Lindel, Katja (Strahlentherapie und Onkologie, 2016)
PurposeThe aim of this work was to evaluate outcomes and toxicities of high dose-rate (HDR) endoluminal brachytherapy in a cohort of esophageal cancer patients.Patients and methodsWe analyzed the records of 36 patients treated with HDR brachytherapy for histologically confirmed esophageal cancer. Brachytherapy was either applied as a boost treatment for definitive treatment regimens or as salvage therapy for recurrent tumors with single doses between 4 and 6 Gy. Survival and toxicities were retrospectively analyzed.ResultsBrachytherapy was performed as initially planned in all but one patient; 18 patients had a complete endoscopic response at the first follow-up examination. Locoregional recurrence was observed in 24 patients after a median time of 3 months; 1‑ and 2‑year recurrence-free survival rates were 51 and 51 % for the patients treated for primary tumors and 11 and 6 % for patients treated for tumor recurrence, respectively. Median overall survival was 18 months; estimated overall survival rates at 1, 2, and 3 years were 63, 50, and 30 % after primary brachytherapy, and 60, 25, and 6 % after recurrence therapy. Adenocarcinoma histology, non-complete remission after treatment, and treatment for recurrent cancers were associated with significantly reduced prognoses. Mild dysphagia was the most common side effect in 17 patients; 8 patients suffered from locoregional grade 3 toxicities, and no grade 4 or 5 toxicities were observed.ConclusionsEndoluminal brachytherapy during the course of esophageal cancer treatment can be safely applied and results in good functional outcomes regarding dysphagia with low rates of severe toxicities.
Gesehen am 19.03.2018